Exploring Utilisation of The Metaverse to Strengthen Indonesian Economic Diplomacy - Shiela Riezqia (International Journal of Economics Development Research (IJEDR), 2023)
Foreign public and private entities have been utilising the Metaverse for economic purposes. However, Indonesia has not fully utilised it. This paper argues that Indonesian Foreign Ministry and diplomats should explore utilisation of the Metaverse to advance Indonesian economic diplomacy. Not doing so may trap Indonesia as a mere market and hinder Indonesia from economic innovation. This paper demonstrates 3 (three) main findings, there are 1) there are existing gap, potentials, and opportunities of Metaverse economy; 2) other countries have been utilizing Metaverse, as best practices and lessons for Indonesia to learn; 3) while there are opportunities, like many other advancements, there are risks that must be managed. This paper proposes interconnected policy choices, there are 1) to increase awareness on the Metaverse Economy in the Ministry of Foreign Affairs of the Republic of Indonesia; 2) to develop policy review and analysis about utilisation of Metaverse for Indonesian economic diplomacy; 3) to embed Metaverse exploration into Indonesian Ministry of Foreign Affairs’ Strategy (Rencana Strategi/Renstra Kemlu RI); and 4) to explore international cooperation. Because the policy choices are highly intertwined, this paper recommends implementing the choices in 2 (two) time frames. A short-term period of 2 (two) years, from 2024 to 2025 by implementing the 1st, 2nd, and 3rd policies. A long-term period of 5 (five) years, from 2024 to 2028, by implementing the 4th policy, together with the first three policies. In conclusion, Indonesian Foreign Ministry and diplomats should explore utilisation of the Metaverse. Not doing so may bring setbacks to Indonesian economy and development, because Indonesia may lose market share and economic opportunities for investment, job creation, innovation, competitiveness, and may fall behind other countries.